Penerapan Bimbingan Rohani Islam Terhadap Narapidana Narkoba di Lembaga Permasyarakatan Kelas II B Kabupaten Sinjai - Tamsil tamsil; Mahmuddin; Arifuddin Tike (Institut Agama Islam Negeri Padangsidimpuan, 2022)
This study aims to determine the application of Islamic spiritual guidance to drug convicts at the Class II B Correctional Institution in Sinjai Regency. This research is a type of qualitative descriptive research. Data collection techniques through observation, interviews and documentation. The sampling technique used was purposive sampling. The data analysis technique is the Milles Huberman analysis technique, namely data reduction (data reduction), data display (data presentation) and verification (drawing conclusions). The results of this study indicate that Islamic spiritual guidance has been running well enough. Islamic spiritual guidance carried out by Islamic spiritual mentors, namely the application of Islamic spiritual guidance methods and the delivery of Islamic spiritual guidance materials. the methods applied in correctional institutions are the religious lecture method, learning the Qur'an and its contents, tahfiz memorizing the Qur'an, the question and answer method, the group discussion method and the enlightenment method. while the material applied is aqidah, worship, morals and muamalah material as well as additional material, namely hadith interpretation, interpretation and tahfidz al-quran, monotheism, fiqh, and general taklim.